Star Wars. Clone troopers in action - Hibbert, Clare, 1970- (Dorling Kindersley readers. Beginning to read alone., 2010)
Tells the story of the clone troopers in "Star Wars: Attack Of The Clones" and how they were created on Kamino as clones of Jengo Fett to do battle against the separatists.